The Prevalence and the Associated Sociodemographic-Occupational Factors of Professional Burnout Among Health Professionals During COVID-19 Pandemic in Malang, Indonesia: A Cross-Sectional Study - Daryanto, Besut; Putri, Frilya Rachma; Kurniawan, Jemmy; Ilmawan, Muhammad; Fajar, Jonny Karunia (Frontiers in Public Health, 2022)
Background: Since 2020, Indonesian health professionals were affected by burnout as the physiological impact due to the COVID-19 pandemic. Malang has a contribution to substantial number of new daily cases and death rates in East Java, an epicenter of COVID-19 in Indonesia. However, study about how burnout affected Malang health professionals was never conducted. Objectives: This research aimed to assess the prevalence and factors associated with burnout among health professionals during the COVID-19 pandemic in Malang, Indonesia. Materials and Methods: A cross-sectional study was carried out with an online survey conducted in 5 Major Hospitals in Malang. We conducted a study about the prevalence rate of burnout in Malang and the association between sociodemographic factors, occupational hazards, and Maslach Burnout Inventory - Human Services Survey (MBI-HSS). The associations were presented as odds ratio (OR) and 95% confidence interval (CI). Result: We analyzed 1,077 health professionals in Malang. Our result showed that the prevalence of burnout among health professionals in Malang is 22.0%. Respondents under the age of 30 tend to experience higher level of burnout by 3.4-fold (OR=3.43, p-value < 0.001), compared to those over the age of 40. Our data also showed that respondents working longer than 100 hours per week tend to experience burnout by 3.8-fold (OR=3.83, p-value < 0.001). Conclusion: Approximately one-fifth of health professionals in Malang suffered from burnout during the COVID-19 pandemic and MBI-HSS subscales strongly associated with age and work hours.